Suicidal ideation in people with tinnitus: a systematic review and meta-analysis. Issue 12 (25th December 2021) - Tailor, B V; Thompson, R E; Nunney, I; Agius, M; Phillips, J S
Abstract: Objective: Tinnitus is associated with a variety of cognitive, psychosocial and psychiatric disorders, and may contribute to suicidality. However, the prevalence of suicidal ideation (SI) in tinnitus populations has not previously been systematically reviewed. Method: Medline, Embase and PsychInfo were searched in August 2020 to identify studies that assessed suicidal ideation in people aged 16 years and above with subjective tinnitus. Results: Six cross-sectional studies were included, representing 7192 tinnitus sufferers across 4 countries. The pooled prevalence of suicidal ideation in tinnitus populations was 20.6 per cent (95 per cent confidence interval, 10.8–30.3 per cent; I 2 = 88 per cent). Two studies included a control population, in which the prevalence of suicidal ideation was significantly lower. The quality of included studies was variable. Conclusion: It is not possible to arrive at any reasonable conclusion given the lack of quality studies, meaning the pooled prevalence should be interpreted very cautiously. Suicidal ideation may be more prevalent in tinnitus populations. Further large-scale epidemiological research investigating this relationship is needed, which may help psychiatric risk stratification.